A Desain Karakter Board Game Pengenalan Fauna Bagi Anak SLow Learner - Andika Perdana Putra; Masnuna; Widyasari (JPI (Jurnal Pendidikan Inklusi), 2026)
Education for slow learners requires special strategies due to intellectual and emotional barriers, such as anxiety and low self-confidence, which hinder the process of information digestion. This study aims to design character designs in the board game "ZooQuest" as an adaptive learning medium for fauna introduction for slow learner students at the elementary school level. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data were collected through interviews with special assistant teachers, observations of the teaching and learning process at Cikal Surabaya School, and literature studies. The results of the study indicate that the design of four main characters (Bobo, Jojo, Cici, and Mimi) with a chibi visual style and "little researcher" attributes is able to transform abstract material into concrete role-playing experiences. These characters function as an emotional bridge that increases student engagement and stimulates verbal communication through cooperative game mechanisms. The conclusion of this study is that character designs adapted to child psychology are effective in supporting the cognitive abilities and social interactions of slow learner students, making them suitable for use as a reference for inclusive learning media